2022
DOI: 10.1038/s41598-022-10280-2
|View full text |Cite
|
Sign up to set email alerts
|

MoS2-based absorbers with whole visible spectrum coverage and high efficiency

Abstract: To design highly efficient and broadband nanometer-sized absorbers based on the atomically thin transition metal dichalcogenides (TMDCs), we propose utilizing inclined gold gratings on MoS2 monolayer. In the case of gold gratings with zero inclination, coverage of the absorption spectrum in the entire visible range occurs between the values of 42% to 73%. Considerable increase in the absorbed light occurs by introducing 13 nm inclination to the gold gratings with equal values of the grating’s period and width … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…In 2017 Wang et al fabricated a 3D perovskite and 2D MoS 2 -based photodetector and demonstrated that the ON/OFF ratio of a photodetector can be improved in the photodetectors by including the 2H phase into the device rather than 1T phase of 2D MoS 2 . [37] In 2019 Ranbir et al studied the 3D perovskite MAPbI 3 solar cell with CVD-grown MoS 2 as the ETL and Spiro-OMeTAD as the HTL and reported 13.2% PCE, comparable to the PCEs achieved from SnO 2 and compact TiO 2 ETL-based PSCs, [38] which was attributed to the wide transmission in the visible spectrum from 400 to 780 nm, [46] with absorption efficiencies above 77% and maximum of 88% of MoS 2 . [38] In 2020 Zhiyong et al investigated the PSC with MoS 2 serving as both an additive as well as BL between PEDOT:PSS and perovskite.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In 2017 Wang et al fabricated a 3D perovskite and 2D MoS 2 -based photodetector and demonstrated that the ON/OFF ratio of a photodetector can be improved in the photodetectors by including the 2H phase into the device rather than 1T phase of 2D MoS 2 . [37] In 2019 Ranbir et al studied the 3D perovskite MAPbI 3 solar cell with CVD-grown MoS 2 as the ETL and Spiro-OMeTAD as the HTL and reported 13.2% PCE, comparable to the PCEs achieved from SnO 2 and compact TiO 2 ETL-based PSCs, [38] which was attributed to the wide transmission in the visible spectrum from 400 to 780 nm, [46] with absorption efficiencies above 77% and maximum of 88% of MoS 2 . [38] In 2020 Zhiyong et al investigated the PSC with MoS 2 serving as both an additive as well as BL between PEDOT:PSS and perovskite.…”
Section: Introductionmentioning
confidence: 97%
“…[ 37 ] In 2019 Ranbir et al. studied the 3D perovskite MAPbI 3 solar cell with CVD‐grown MoS 2 as the ETL and Spiro‐OMeTAD as the HTL and reported 13.2% PCE, comparable to the PCEs achieved from SnO 2 and compact TiO 2 ETL‐based PSCs, [ 38 ] which was attributed to the wide transmission in the visible spectrum from 400 to 780 nm, [ 46 ] with absorption efficiencies above 77% and maximum of 88% of MoS 2 . [ 38 ] In 2020 Zhiyong et al.…”
Section: Introductionmentioning
confidence: 99%
“…For comparison, broadband metamaterial absorbers (BMAs) possess the essential ability of near-perfect absorption across a spectrum continuum. More importantly, their absorption bandwidth can be further expanded through proper engineering operations, and even across some specific spectral regions, such as near-perfect absorption in the visible region, [65][66][67] providing enough possibility for full capture and benefit of solar energy. Figure 1 shows the summarization of some crucial achievements in the field of MAs, especially the BMAs, from 2008 to the end of 2022.…”
Section: Introductionmentioning
confidence: 99%
“…However, similar to graphene and other 2D materials, 9 the atomic thickness of 2D MoS 2 leads to low optical absorption in the visible and especially near-infrared (NIR) regime, which limits its potential to serve as an efficient photodetector or photovoltaic device. 10 Conventional photon management strategies for 2D materials such as Fabry−Peŕot microcavity 11 or guided resonance in the photonic crystal 12 would need complicated fabrication processes and the enhanced light absorption only covers a relatively narrow spectral range. On the other hand, while multilayer MoS 2 has been applied to achieve broadband photoresponse from 450 to 2700 nm, 13 quantum efficiency is still limited to ∼10% in the visible regime (at λ ∼ 500 nm) and <5% in the NIR regime at λ > 800 nm.…”
Section: Introductionmentioning
confidence: 99%
“…However, similar to graphene and other 2D materials, the atomic thickness of 2D MoS 2 leads to low optical absorption in the visible and especially near-infrared (NIR) regime, which limits its potential to serve as an efficient photodetector or photovoltaic device . Conventional photon management strategies for 2D materials such as Fabry–Pérot microcavity or guided resonance in the photonic crystal would need complicated fabrication processes and the enhanced light absorption only covers a relatively narrow spectral range.…”
Section: Introductionmentioning
confidence: 99%